2016
DOI: 10.1098/rsos.160375
|View full text |Cite
|
Sign up to set email alerts
|

The role of three heat shock protein genes in the immune response to Aeromonas hydrophila challenge in marbled eel, Anguilla marmorata

Abstract: Heat shock proteins (HSPs) are highly conserved molecular chaperones that play critical roles in both innate and adaptive immunity. However, little information about HSPs from marbled eel Anguilla marmorata is known. In this study, the full-length Amhsp90 (2527 bp), Amhsp70 (2443 bp) and Amhsc70 (2247 bp) were first cloned from A. marmorata, using rapid amplification of cDNA ends, containing open reading frames of 2181, 1932 and 1950 bp in length, and encoding proteins with 726, 643 and 649 amino acids, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Wang et al (2007) observed its up-regulation among HSPs expressed in summer in goldfish and its expression was higher in gills than liver. We also observed that its summer level of expression is higher than winter but liver level exceed gills which may be attributed to species difference in regulatory roles of HSPs (Liang et al, 2016).…”
Section: Micronucleus Assaymentioning
confidence: 72%
“…Wang et al (2007) observed its up-regulation among HSPs expressed in summer in goldfish and its expression was higher in gills than liver. We also observed that its summer level of expression is higher than winter but liver level exceed gills which may be attributed to species difference in regulatory roles of HSPs (Liang et al, 2016).…”
Section: Micronucleus Assaymentioning
confidence: 72%
“…Generally, heat shock proteins are constitutively expressed in cells to maintain a number of critical cellular processes relating to protein folding, fidelity and translocation with the task to ensure survival by protecting vital cellular functions [ 67 ]. As such, this family of proteins is also commonly referred to as “stress/repair proteins” and an upregulation of hsp90 has been previously described in several fish species, including the responses of silver sea bream ( Sparus sarba ) to Vibrio alginolyticus [ 68 ], miiuy croaker ( Miichthys miiuy ) to Vibrio anguillarum [ 69 ], and marbled eel ( Anguilla marmorata ) to Aeromonas hydrophila [ 70 ]. Thus, in the present study, the upregulation of hsp90 observed on 22 dph, might be a response to the presence of potentially harmful bacteria in the larval bacterial community, triggering the activation of the stress/repair mechanism, which might be of key essence, especially considering that the larval immunocompetence is not yet fully developed.…”
Section: Discussionmentioning
confidence: 99%